Measurements of noise at crossroads and on transportations, its effects and possible measures to take - (:unkn) unknown (JOURNAL VIBROENGINEERING, 2011)
Noise has some effects which can be explained under the titles as 'psychological', 'physical', 'physiological', and 'related to performance'. The psychological effects are general feeling of annoyance, boredom, bad-temper, and behavioural disorders; the physiological effects are the increase in blood pressure, faster breathing and pulsation, changes in body activities, disorders in blood circulation and sudden reflexes. The physical effects are temporary or permanent hearing damage. The effects on performance are associated with difficulty in concentration, lack of movement, and decrease in efficiency at work. It may not be possible to keep noise at normal levels in every condition but it may be possible to keep its effects under control by various arrangements and preventions. The measurement and definition of the noise, desired to be kept under control, by accurate methods and systems is a determinative factor in prevention of noise. For this aim the noise measurements were applied in Kadikoy, on the Anatolian Side of the city of Istanbul. In the research the measurements were made on five major crossroads and on mass transportations and the results were analyzed. The time of the measurements was randomly selected within working hours on weekdays. The data were obtained at certain periods of time from different spots and the results were presented.
Keywords: noise; traffic; city noise; noise measurement